Studi Alkitab tentang Misi dan Pemuridan dalam Amanat Agung dan Implikasinya Bagi Kehidupan Kristen Masa Kini - Yonatan Alex Arifianto; Reni Triposa; Paulus Karaeng Lembongan (Bethel Press, 2020)
Abstract Christianity in the spiritual growth and quantity of the church cannot be separated from believers who carry out the mandate of the Great Commission. But in the accompanying journey of God there is not much that can be done by believers in mission and discipleship. So with that focus and purpose of this research is to answer the research question of how the Bible study of mission and discipleship in the Great Commission and its implications for Christian life today. While the problem that occurs in this research work is how Discipleship and mission are not properly understood in the current era so that many prioritize mission but override discipleship or vice versa. But the benefits of this research are: first, the importance of mission in the Great Commission, then the importance of discipleship for believers and continuity and the last implies mission and discipleship as life priorities. To describe the biblical study of mission and discipleship in the Great Commission and its implications for contemporary Christian life, researchers used library research methods with quantitative descriptive approaches.